0049 Screen time and sleep in young adolescents before and across the first year of the COVID-19 pandemic. (25th May 2022) - Kiss, Orsolya; de Zambotti, Massimiliano; Schaefer, Emil; Durley, Ingrid; Kerr, Erin; Dulai, Teji; Arra, Nicole; Obilor, Todd; Camacho, Leticia; Hsu, Carrie; Baker, Fiona
Abstract: Introduction: The COVID-19 pandemic has been associated with profound biopsychosocial changes for children, potentially affecting their health and wellbeing. Among these changes are altered sleep patterns and screen time use, however, no work has examined interactions between these two behaviors in the context of the pandemic. Here, we used longitudinal data from the Adolescent Brain Cognitive Development (ABCD) Study® to investigate changes in both sleep and screen time, and their relationship, from before and across the first year of the COVID-19 pandemic in young adolescents. Methods: More than 5000 adolescents (11-14 years; 48% girls) completed digital surveys about their sleep and daily screen time use before the pandemic and across six timepoints during 2020-2021, as part of the ongoing ABCD Study®. Random intercept linear mixed effect models (LMMs) were used to examine longitudinal associations between bedtime, wake-up time, and daily screen time use (social media, gaming), considering age, sex, and school effects. Results: Adolescents' wake up time was delayed (R2 = 0.51; ~1.5 hour) during May-August 2020 relative to the pre-pandemic assessment (p<0.01), which was partially related to the summer break (p<0.01), before advancing to earlier times in October 2020. Bedtimes also delayed at all pandemic assessments (R2=0.62; ~1 hour), even after starting the new school year (p<0.01), particularly in older adolescents (p<0.01) and girls (p<0.01). Recreational screen time was dramatically higher across the first year of the pandemic, relative to pre-pandemic (p<0.01; ~45min social media, ~20min video gaming). More time spent with screen related activities was associated with later bedtimes and wake up times (p<0.01), across the pandemic, with effects being evident in male and female adolescents. Conclusion: Our findings show profound changes in sleep timing and screen time use across the pandemic in young adolescents, and critically, that excessive screen time negatively impacts sleep. As adolescents increasingly turn to more screen usage, these data highlight the need to promote their balanced and informed use of social media platforms, video games, and other digital technology to ensure adequate opportunity to sleep and maintain other healthy behaviors during this critical period of developmental change. Support (If Any): NIH U01DA041022